2002
DOI: 10.1046/j.1464-5491.2002.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of screening policies for diabetic retinopathy using simulation

Abstract: The model can evaluate screening intervals and methods on a national or health authority basis. Results indicate that it appears more cost effective to continue to screen outside an ophthalmology clinic, until treatment is needed. Programmes with annual screening, and more frequent screening for those with background retinopathy, are robust to realistic fluctuations in compliance and screening sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 58 publications
1
57
1
2
Order By: Relevance
“…However, in contrast to these two studies, another UK study by Davies et al 48 found that screening diabetic patients less than once a year would not be any more cost-effective than every year. Davies et al 48 also based their study on a decision analytic model populated using results obtained from the published literature. A finding common in both UK studies was that screening of type 1 diabetes patients was more cost-effective than screening of type 2 diabetes patients.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, in contrast to these two studies, another UK study by Davies et al 48 found that screening diabetic patients less than once a year would not be any more cost-effective than every year. Davies et al 48 also based their study on a decision analytic model populated using results obtained from the published literature. A finding common in both UK studies was that screening of type 1 diabetes patients was more cost-effective than screening of type 2 diabetes patients.…”
Section: Introductionmentioning
confidence: 69%
“…The study, which also used a decision analytic model to assess the cost-effectiveness of DR screening in both type 1 and type 2 diabetes patients, found that a 30-month screening interval was the most cost-effective option. However, in contrast to these two studies, Davies et al 48 found that screening diabetic patients less than once a year would not be any more cost-effective than screening them every year. The study also based its work on a decision analytic model populated using results obtained from the published literature.…”
Section: Existing Researchmentioning
confidence: 83%
“…Such models incorporate a number of assumptions including prevalence, incidence and natural history of diabetes and DR, screening sensitivity and specificity, patient compliance, and treatment efficacy. Davies et al modelled screening strategies to determine cost-effectiveness in a population of 500,000 821 . Standard methods of screening save up to 50% of the sight years potentially lost.…”
Section: International Datamentioning
confidence: 99%
“…An idealised gold standard program using mydriatic seven-field photography reported by an ophthalmologist save up to 85% of sight years potentially lost. Screening by a mobile camera (one photo reviewed by a diabetologist) gave the lowest cost of sight years saved (£2842) 821 . It is less effective to screen type 2 than type 1 diabetes patients, but type 2 patients contributed to almost three-quarters of the sight years saved.…”
Section: International Datamentioning
confidence: 99%
“…Although the cumulative risk of retinopathy is substantial in type I DM, reaching up to 60% for sightthreatening disease over 20 years, the overall burden of preventable blindness secondary to type II DM is greater, because its prevalence is higher. 1,2 The prevalence of DM, particularly type II DM, is rising throughout the world and especially in developed countries. 3 In England and Wales, diabetic retinopathy remains the most common cause of blindness registration among people of working age.…”
Section: Introductionmentioning
confidence: 99%